A Short Return to Simple Ah-Algebras with Real Rank Zero - Lin, Huaxin (MATHEMATICA SCANDINAVICA, 2014)
Let A be a unital simple AH-algebra with stable rank one and real rank zero such that kx=0 for all xkerρ_A, the subgroup of infinitesmal elements in K_0(A), and for the same integer k1. We show that A has tracial rank zero and is isomorphic to a unital simple AH-algebra with no dimension growth.